THE INFLUENCE OF COMPETENCY OF HUMAN RESOURCES, IMPLEMENTATION OF FINANCIAL APPLICATION, AND IMPLEMENTATION OF GOVERNMENT ACCOUNTING STANDARD ON FINANCIAL STATEMENT QUALITY WITH ORGANIZATIONAL COMMITMENT AS MODERATING VARIABLE - Fahdi, Fauzi Nasution (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to analyze the influence of competency of human resources, implementation of financial application, and implementation of government accounting standard on financial statement quality with organizational commitment as moderating variable. The research used causal method. The population was 35 SKPDs (Regional Work Units) which consisted of Financial Administrative Personnel and the staffs in the Finance Department in the North Sumatera Provincial Administration. The samples were 70 respondents, taken by using census sampling technique. Primary data were gathered by using questionnaires and processed by using multiple linear regression analysis. The result of the research showed that, simultaneously and partially, there was positive and significant influence of competency of human resources, implementation of financial application, and implementation of government accounting standard on financial statement quality in the North Sumatera Provincial Administration. Organizational commitment could moderate the correlation of the influence of competency of human resources, implementation of financial application, and implementation of government accounting standard with financial statement quality in the North Sumatera Provincial Administration.